Does family control reduce firm risk? - Miralles-Marcelo, José Luís (2018)
In the current context of instability and financial crisis, understanding firm risk is crucial. In this study we aim to assess firm risk differences between family and non-family firms. Furthermore we analyze the family control impact, measured by both the family ownership and the F-PEC scale, in firm risk. We provide new evidence from family firm studies since we not only analyze the risk topic, almost unexplored, but we also introduce the F-PEC scale, an alternative way to measure the family influence. Using Portuguese quoted firms during the 1999-2012 period, we find that family influence and control do not impact firm risk. Moreover, the firm size, return and growth opportunities influence it.